MicroRNA-223-3p is involved in fracture healing by regulating fibroblast growth factor receptor 2 - Bin Wang (Taylor & Francis Group, 2021)
MicroRNAs (miRNAs) are powerful modulators of fracture healing. The research explored the level of serum miR-223-3p in fracture patients and its potential mechanism in fracture healing. In the study, miR-223-3p levels in 42 patients with intra-articular fracture and 40 patients with hand fracture were detected by real-time fluorescence quantitative PCR reaction (qRT-PCR). Subsequently, osteoblasts MC3T3-E1 was transfected with miR-223-3p mimic or inhibitor, and cell function was detected by Cell counting kit (CCK-8) assay and flow cytometry. Dual-luciferase reporter assay verified the regulation mechanism of miR-223-3p and its target genes. We found that miR-223-3p was significantly elevated over time in patients with intra-articular fracture and hand fracture patients compared with healthy individuals. Moreover, increased miR-223-3p significantly reduced cell viability and promoted cell apoptosis. The fibroblast growth factor receptor 2 (FGFR2) was the target of miR-223-3p. Serum FGFR2 was significantly decreased in patients, which was contrary to the expression of miR-223-3p. Moreover, FGFR2 levels in cells were negatively regulated by miR-223-3p. Finally, si-FGFR2 significantly reversed the promotion of miR-223-3p inhibitor on cell viability and the inhibition of cell apoptosis. Our research suggested that miR-223-3p is highly expressed in fracture patients, and regulates osteoblast cell viability and apoptosis by targeting FGFR2. This may be a valuable target for fracture healing therapy and provide a new perspective for its treatment.